Beyond the State: Pesantren Networks as Shadow Diplomatic Infrastructure in Indonesia-Malaysia Relations - Muhammad Fikri Amra (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
This paper examines the role of pesantren networks as informal diplomatic channels between Indonesia and Malaysia, conceptualizing them as "shadow diplomatic infrastructure" that operates parallel to official state mechanisms. Drawing on institutional analysis and empirical evidence, this study demonstrates how transnational Islamic educational networks have facilitated continuous cross-border engagement, particularly during periods of bilateral tension. The research reveals that pesantren networks, anchored in shared religious traditions and genealogical ties among ulama, constitute a resilient form of Track II diplomacy that predates modern nation-states. Through examination of key pesantren institutions and their regional linkages, this paper argues that these networks provide alternative pathways for bilateral engagement that complement, and occasionally substitute for, formal diplomatic channels. The findings contribute to broader debates on non-state actors in international relations and challenge state-centric frameworks for understanding Southeast Asian regionalism.